2016
DOI: 10.1038/cmi.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Arterial thrombosis in the context of HCV-associated vascular disease can be prevented by protein C

Abstract: Hepatitis C virus (HCV) infection is a major problem worldwide. HCV is not limited to liver disease but is frequently complicated by immune-mediated extrahepatic manifestations such as glomerulonephritis or vasculitis. A fatal complication of HCV-associated vascular disease is thrombosis. Polyriboinosinic:polyribocytidylic acid (poly (I:C)), a synthetic analog of viral RNA, induces a Toll-like receptor 3 (TLR3)-dependent arteriolar thrombosis without significant thrombus formation in venules in vivo. These pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…TLR-3 expression on platelets and megakaryocytes has been reported and its ligation on platelets can potentiate platelet aggregation by other classical platelet agonists (46). The use of Poly I:C for studying thrombosis is not as widespread as for other models, but injection with Poly I:C has been described to induce TLR-3-dependent arterial thrombosis, but a more minimal thrombosis in the venules (47). As there is limited data for the use of Poly I:C in this context, more work is needed to better understand the strengths and limitations of its use to recapitulate what is observed after viral infection.…”
Section: Models To Study Thrombosis Induced By Infectionmentioning
confidence: 99%
“…TLR-3 expression on platelets and megakaryocytes has been reported and its ligation on platelets can potentiate platelet aggregation by other classical platelet agonists (46). The use of Poly I:C for studying thrombosis is not as widespread as for other models, but injection with Poly I:C has been described to induce TLR-3-dependent arterial thrombosis, but a more minimal thrombosis in the venules (47). As there is limited data for the use of Poly I:C in this context, more work is needed to better understand the strengths and limitations of its use to recapitulate what is observed after viral infection.…”
Section: Models To Study Thrombosis Induced By Infectionmentioning
confidence: 99%
“…MC participates in both mechanisms. Indeed, MCs were demonstrated to be targeted by various viruses [ 212 , 214 , 219 , 279 , 280 , 281 , 282 , 283 ]. First, HIV was shown to infect MCs [ 212 ] with an orphan G protein-coupled receptor 1 (GPR1) as a co-receptor [ 213 ].…”
Section: Msc Viral Infection and Host Responsesmentioning
confidence: 99%
“…The pathology associated with HCV is mostly liver disease, but with frequent extrahepatic complications, such as glomerulonephritis. HCV triggers TLR3 activation of MC leading to the release of procoagulant factors that causes vascular thrombosis and finally glomerulonephritis [ 279 ]. Furthermore, MCs may be infected by ZIKV.…”
Section: Msc Viral Infection and Host Responsesmentioning
confidence: 99%
“…IL-1β secretion required longer stimulation [ 177 ]. However, another set of experiments suggested that the poly(I:C) stimulation of platelets did not induce platelet aggregation or activation [ 178 ]. Thus, TLR3-stimulation could potentiate platelet aggregation upon hemostatic stimulation, rather than inducing aggregation by itself, as evidenced by D’Atri et al [ 177 ].…”
Section: Platelets As Immune Cellsmentioning
confidence: 99%